TPM1-p.E181K mutation suppresses CaMKII/HDAC4 signaling pathway leading to pediatric restrictive cardiomyopathy - Fu, Jia; Zhang, Jing; Zhang, Youxian; Sun, Dongming; Xia, Kun; Wang, Ruigeng; Feng, Xiaoyuan; Zhai, Aiguo; Huang, Yufeng; Li, Xiaobin; Yu, Wenjun; Zhang, Yong (Frontiers in Genetics, 2026)
BackgroundThis study aims to elucidate the pathogenicity of the TPM1 mutation (NM_001018005.2:c.541G>A, p. Glu181Lys) in restrictive cardiomyopathy (RCM), establish its ACMG pathogenicity classification, and report for the first time its association with sporadic RCM and underlying molecular mechanisms. The research focuses on delineating how this mutation triggers myocardial pathology via disruption of the CaMKII/HDAC4 signaling pathway.MethodsProtein 3D modeling predicted structural alterations induced by the mutation. TPM1-wild-type (WT) and mutant (p.E181K) plasmids were transfected into AC16 cardiomyocyte cell lines. Quantitative PCR (qPCR) and Western blotting (WB) analyzed gene/protein expression levels. Intracellular calcium transients were detected using Rhod-2 AM fluorescent probes. F-actin cytoskeletal reorganization was assessed by Phalloidin-488 staining. Phosphorylation status of key CaMKII/HDAC4 pathway components and troponin (Tn) activity were evaluated to define functional mechanisms.ResultsBioinformatic analysis revealed disruption of hydrogen bonding and electrostatic potential at the mutation site. TPM1-p.E181K did not alter overall protein expression or mitochondrial activity but significantly suppressed intracellular Ca2+ transients and inhibited CaMKII/HDAC4 phosphorylation. Impaired troponin activity and abnormal cardiomyocyte contractility were observed.ConclusionThis study establishes a novel link between TPM1-p.E181K and sporadic RCM. We demonstrate that its pathogenesis is mediated through a cascade of events: calcium dyshomeostasis leads to the suppression of CaMKII/HDAC4 phosphorylation, which subsequently causes sarcomere structural disruption, and ultimately results in myocardial hypercontractility. This identified signaling axis may represent a promising therapeutic target for RCM.